EXERGY ANALYSIS ON THERMAL POWER PLANT PT. MAKASSAR TENE USING CYCLE-TEMPO 5 - La Ode Musa; Apollo Apollo; Aini Syahrunnisa; Muhammad Yusuf (Jurnal Teknik Mesin Sinergi, 2018)
Analyzing exergy on the power plant generating system specially at PLTU, efficient utilization of energy resources can be obtained particularly since it leads efforts to reduce energy waste that already exists.The purposes of this research are to get the Thermal Power Plant system modeling of PT. Makassar Tene, to get the value of modeled exergy power plant system, to get exergy losses, to get the amount exergy efficiency and to get the cost of exergy losses.The research method was firstly, designing the Power Plant generating systems PT. Makassar Tene using Cycle-Tempo 5 as thermodynamic analysis tool. Results of calculations were then used to calculate the exergy profile.Exergy values analyzed on a system modeled Power Plant consists of turbine components, condensers and pump. Boilers are not included in the analysis because of the input device is not contained and the mass flow rate of the boiler occurs steady state in which the state of the same process with the state of the environment so that there is no exergy difference that can be utilized.The highest exergy losses based on the modelling was on the turbine components that was 10201.50 kW. This was due to the change in the vapor phase into the liquid phase contained in the component before and after leaving the turbine components. While the lowest exergy losses was on the pump component, that was 437.18 kW.The higher the efficiency value of a component, the better its performance is. The highest efficiency value of exergy that was 51.43% contained on the turbine components. While the lowest efficiency value of exergy was 0%.